Analysis of Learning Styles of Academically Achieving Students - Delina, E. Jeli; Apdoludin, Apdoludin; Aldino, Aldino (Journal La Sociale, 2025)
This study investigates the learning styles of academically high-achieving students at SD Negeri 138/II Daya Murni, aiming to understand how these preferences influence their academic success. Employing a qualitative descriptive approach, the research was conducted from June to August 2025. The study's subjects, selected through purposive sampling, included two high-achieving students and their Class V homeroom teacher. Data were collected using method triangulation, comprising participatory observations, structured interviews, and documentation. The data were then analyzed using a descriptive analysis technique involving data reduction, presentation, and verification. The key findings indicate that while students utilized a combination of visual, auditory, and kinesthetic styles, their academic achievement was predominantly driven by the effective application of visual and auditory learning. The study concludes that an understanding and accommodation of these dominant learning styles, alongside a supportive learning environment, are crucial for fostering and sustaining high academic performance.